Handling uncertainty in health care management using the cardinality-constrained approach: Advantages and remarks. (March 2015) - Addis, Bernardetta; Carello, Giuliana; Grosso, Andrea; Lanzarone, Ettore; Mattia, Sara; Tànfani, Elena
Abstract: Different approaches have been proposed in the literature to handle uncertain parameters in health care optimisation problems. Among them, the cardinality-constrained approach to robust optimisation seems suitable for handling several of these problems because it allows a trade-off between the level of robustness and the cost of the solution, and an easy implementation that can be understood by clinicians and planners without any background in operations research. Thus far, however, cardinality-constrained approach has rarely been applied to health care. We recently applied the cardinality-constrained approach to two relevant health care management problems, namely, the operating room planning problem and the nurse-to-patient assignment problem in home care services. In this communication, we briefly describe our experience and focus on general considerations, advantages, and remarks that can help operations researchers in evaluating the approach for other applications in health care management.